Elevated temperature electrochemical studies of preoxidized nickel electrodes in the presence of sulfide - Streeter, I; Giovanelli, D; Wildgoose, G; Lawrence, N; Jiang, L; Jones, T; Compton, R (2004)
The electrochemical response of a preoxidized nickel electrode to increasing additions of sulfide has been examined over temperature range from 25 to 70°C. In the presence of sulfide a stripping like response was observed at all temperatures. The results detailed show that as the temperature is increased the sensitivity increases from 3.4 to 13.5 A M-1 for the determination of sulfide.